Fish-based products in diverse aquatic systems: Innovating with product development to tackle malnutrition and improve livelihoods - Bonis-Profumo, Gianna; Hunnam, Kimberly; Wate, Jillian Tutuo; Batalofo, Margaret; Duarte, Agustinha; Ou, Phichong; Rizaldo, Quennie; Khan, A K M Firoz; Ratha, Baishnaba; Shenoy, Neetha; Mudege, Netsayi; Gichohi, Wanjiku; et al. (WorldFish, 2024)
This brief summarizes WorldFish’s work on fish-based products in seven countries across three continents over the past 10 years. It is based on an e-learning event that brought country teams together to document approaches, lessons and research priorities. Fish-based products are a cornerstone of WorldFish’s work. Piloting and/or scaling products such as dried fish and fish powder have been a core component of its aquatic food system research for development and nutrition-sensitive programs, providing a link between production systems and consumer well-being.